POPULATION DYNAMICS OF COLLEMBOLA AND ACARI IN WETLANDS AND CROPLANDS IN INDO-GANGETIC PLAINS OF NORTH BIHAR - V. B. LAL,; A. K. SINHA,; S. L. DEZI,; D DEEPTI LAL, (The Bioscan, 2011)
Twelve genera of Collembola belonging to four different families were recorded from cropland field, whereas only eight genera of three different families of Collembola could be recorded from the wetland field. Similarly sixteen different species of mites and a Nova species were found in cropland field whereas only eight species of mites were present in wetland field implying thereby that inundation is not favored by certain species of Collembolans and mites. The impact of water logging on population densities of both the groups of fauna was clearly evidenced. Out of the two peaks exhibited by Collembolan one was more pronounced in the month of September while the other was less pronounced in the month of March in cropland. In wetland higher numbers was observed in the month of March but Water logging rendered zero population of both the groups of soil fauna in the month of August and September. Mites had also a peak in the month of August and March in cropland and wetland fields respectively.